Effect of stress waveform on the rock blasting crack propagation mechanism using numerical simulation - Yong-qi LI; Zheng-zhao LIANG; Xi-kun QIAN; Hong-bo LIU (工程科学学报, 2022)
The type, proportion, and charging method of explosives produce different stress waveforms, which greatly affect rock crack propagation. Because of the complex interaction law between waveform parameters such as the peak value, wavelength, energy, and rise or fall rate, and the limited physical and mechanical test conditions, quantitatively controlling waveform parameters in a blasting test is difficult. Numerical simulation has advantages in revealing the influence law of the stress wave. In this paper, RFPA3D dynamic analysis software was used to simulate the crack propagation in a rock with a prefabricated crack under impact loads, and the effects of the stress wave peak value, energy, rise rate, and fall rate of the stress wave on the rock crack propagation process were investigated. Results show that the rock crack propagation pattern under dynamic loads was affected by the rise rate of the stress wave. The faster the stress wave rose, the more breakages occurred around the hole. For the crack propagation length, the crack grew longer with the increase in the stress wave energy. When the stress wave energy was constant, the crack grew farther with the decrease in the rise rate, but the broken degree around the hole was decreased. The rise rate and the energy of the rising edge of the stress wave affected the radius of the comminution zone. Numerical simulation results revealed the rock crushing mechanism of different stress wave peak values, energies, and rise or fall rates. In a practical engineering blasting operation, to expand the impact range of blasting, extending the action time using a water cannon mud seal or an air column interval charge structure was suggested. In addition, the appropriate type and proportion of explosives were also selected to increase the stress wave’s rise rate to improve the effect of hole edge crushing.